New niches of community rights to forests in Cameroon: tenure reform, decentralization category or something else? - Oyono, P.R. (2009)
In a difficult political economy, marked notably by a multifaceted crisis, Cameroon, like many other African countries, launched the restructuring of the policy and legal framework that governed the management of forest until the mid-1990s. Given the deep conflict of discourse surrounding the issue of forest ownership and rights to forest in Central Africa, the allocation of new niches of community rights to forest is, in theory, meaningful of the emergence of a new type of relations between the ‘central’ and the ‘local’ and, therefore, a new configuration of issues like resource ‘politics’ and resource governance. Unlike West, East or Southern Africa, resource tenure is a not really an old research domain in Central Africa. While injecting information on the topic, the essay interrogates the nature of ongoing change in the structure of community rights to forest in Cameroon. In policy terms, what is really this change? Some call it tenure change, some others call it decentralization. Using conceptual, theoretical and empirical arguments, the essay conducts a policy analysis of both options and concludes that this is neither a strict decentralization process nor a strict tenure reform. It is a mixture of devolution and delegation of powers. Theorists, policy designers and professional must be informed about this dilemma.